2017
DOI: 10.7554/elife.20147
|View full text |Cite
|
Sign up to set email alerts
|

A saturation hypothesis to explain both enhanced and impaired learning with enhanced plasticity

Abstract: Across many studies, animals with enhanced synaptic plasticity exhibit either enhanced or impaired learning, raising a conceptual puzzle: how enhanced plasticity can yield opposite learning outcomes? Here, we show that the recent history of experience can determine whether mice with enhanced plasticity exhibit enhanced or impaired learning in response to the same training. Mice with enhanced cerebellar LTD, due to double knockout (DKO) of MHCI H2-Kb/H2-Db (KbDb−/−), exhibited oculomotor learning deficits. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(60 citation statements)
references
References 76 publications
15
45
0
Order By: Relevance
“…Second, we assessed the local homeostatic action provided by years of age and declining abruptly afterwards, Li et al, 2015, Matiño-Soler et al, 2015 We ran a fourth cross-sectional simulation to assess how the three neuro-synaptic factors would concurrently work during VOR adaptation. The results confirmed that the global homeostatic compensation mediated by cerebellar LTP/LTD was primarily responsible for the non-linear temporal profile observed in VOR epidemiological data (Nguyen-Vu et al, 2017), stating that an intense change of the synaptic strength shall temporarily prevent further adaptation. They showed that a specific type of pre-training that desaturates synapses can improve the ability of mutant mice to learn an eyemovement task.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Second, we assessed the local homeostatic action provided by years of age and declining abruptly afterwards, Li et al, 2015, Matiño-Soler et al, 2015 We ran a fourth cross-sectional simulation to assess how the three neuro-synaptic factors would concurrently work during VOR adaptation. The results confirmed that the global homeostatic compensation mediated by cerebellar LTP/LTD was primarily responsible for the non-linear temporal profile observed in VOR epidemiological data (Nguyen-Vu et al, 2017), stating that an intense change of the synaptic strength shall temporarily prevent further adaptation. They showed that a specific type of pre-training that desaturates synapses can improve the ability of mutant mice to learn an eyemovement task.…”
Section: Discussionsupporting
confidence: 78%
“…We simulated two age groups (20 young subjects: 20 yo; 20 older subjects: 100 yo) and we linearly decreased the inhibitory MVN input to IO as a function of age (from a maximum at 20 years to zero at 100 years, see Methods). We compared the dynamics of IO spatiotemporal firing patterns in a 5x5 lattice configuration (Nobukawa and Nishimura, 2016), when an errorrelated pulse activated the central IO neuron of the network (neuron 1 in Supp. Fig.…”
Section: Olive Neuronsmentioning
confidence: 99%
“…An exception was the study by Schreurs et al (1997) which reported suppression of LTD at PF-PC synapses after classical conditioning in rabbits, although whether amplitudes of synaptic responses were depressed was not examined. We also note that recent study by Nguyen-Vu et al (2017) suggested occurrence of LTD saturation in double knockout mice of MHC1 H2-K b /H2-D b with enhanced LTD.…”
Section: Introductionsupporting
confidence: 56%
“…Since Hebb's rule was proposed, many neuroscientists have focused on the plastic changes in the synaptic neurotransmission within the given synapses such as long-term potentiation and depression (LTP and LTD, respectively) [ 1 2 3 4 5 ]. These persistent alterations of synaptic strength have been suggested to be a cellular basis of memory storage in the brain, which have been supported by the experimental observations in which experience- and use-dependent modulation of the synaptic function are exhibited by certain forms of behavioral training [ 4 6 7 ]. There is, however, accumulating evidence supporting the idea that information storage may also involve the activity-dependent modulation of neuronal intrinsic excitability (intrinsic plasticity) in addition to synaptic plasticity [ 8 9 10 11 12 ].…”
Section: Introductionmentioning
confidence: 81%